2015 XVIII AISEM Annual Conference 2015
DOI: 10.1109/aisem.2015.7066842
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive classification model based on artificial immune system for breast cancer detection

Abstract: Early stage asymmetric signs in breast that can be captured by the screening-digital mammography can be used for a precocious diagnosis of breast cancer. Conventional mammography screening fails to detect subtle anomalies, so computer-aided methods are studied in order to improve the accuracy of image analysis. To classify the images into asymmetric and normal cases, in this paper we investigated the performance of an Adaptive Artificial Immune System (A 2 INET) classifier. To test the efficiency of the algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…SAR automatic target detection methods are mainly divided into two types, i.e., template-based [27]- [29] and model-based methods [30]- [32]. The core of template-based method performs feature extraction and selection, which requires wide professional knowledge as the basis.…”
mentioning
confidence: 99%
“…SAR automatic target detection methods are mainly divided into two types, i.e., template-based [27]- [29] and model-based methods [30]- [32]. The core of template-based method performs feature extraction and selection, which requires wide professional knowledge as the basis.…”
mentioning
confidence: 99%
“…The results showed that the A 2 INET system achieves better results compared to more conventional classifications. The classification accuracy rate in this system is 85% [9]. In the research presented by Pawar and Talbar (2016), the method of co-occurrence wavelet feature selection using the fuzzy system of co-occurrence wavelet feature selection using the fuzzy genetic system is proposed in the problem of classifying mammography images [10].…”
Section: Magenda Et Al (2015) Have Investigated the Classification Pe...mentioning
confidence: 99%
“…Como resultado se obtiene un modelo con un acierto en la clasificación del 90% usando la base de datos de imágenes DDSM mini-MIAS, lo cual muestra mejores resultados en comparación con trabajos que usan los mismos datos como el propuesto en (Magna et al, 2015) con 85% y en (Casti et al, 2015) con 82%.…”
Section: Sistema Inmune Artificial (Ais)unclassified